Environmental conditions: cold - Tipton, M. (Triathlon Medicine, 2019)
The impact of environmental conditions is often overlooked in sport, where the pre-occupation is generally with nutrition and training. However, inappropriate preparation and strategy for the thermal conditions of an event can not only significantly impact on performance, but it can also threaten athlete health and safety. Thus, those organising, supervising as well as competing in triathlon events should be well-versed in the threats associated with the thermal conditions of a triathlon and know how to mitigate and treat them. With this in mind, in this chapter we examine the challenge of cold for triathlon, concentrating on the swim, T1 and the early part of the cycle. We provide advice to help athletes and organisers maintain performance and avoid injury through preparation, protection and event organisation.